Performance Study of a Three Cylinder Reciprocal Piston Expender Driven by Compressed Air as Working Fluid - เทนอิสสระ นพพร; เทพา ศิริชัย; โมนยะกุล วีระพล (Princess of Naradhiwas University Journal, 2019)
This research presents performance of a 831 cc. reciprocal pistol expander engine, using compressed air as working fluid. This engine was modified from 3-pistol diesel engine, in order to evaluate its basic performance. Generally, the result of this work will be used in the future for developing a better Organic Rankine cycle engine. The engine was setup for evaluation with a dynamo driven platform under constant charge pressure at 3 bars, 5 bars and 7 bars, in order to find toque, power and air-flow rate. This was done by varying engine speed, whereas the power was 166 W., 410 W. and 600 W., with 200 rpm. for average speed and an isentropic efficiency of 31%, 49% and 51%, respectively. Under optimal conditions, engine can be used with compressed air to produce electrical energy.